2020
DOI: 10.1002/cnm.3388
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty in model‐based treatment decision support: Applied to aortic valve stenosis

Abstract: Patient outcome in trans-aortic valve implantation (TAVI) therapy partly relies on a patient's haemodynamic properties that cannot be determined from current diagnostic methods alone. In this study, we predict changes in haemodynamic parameters (as a part of patient outcome) after valve replacement treatment in aortic stenosis patients. A framework to incorporate uncertainty in patient-specific model predictions for decision support is presented. A 0D lumped parameter model including the left ventricle, a sten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Previous research has shown promising results for personalizing cardiovascular models [5][6][7][8][9][10][11][12] or predicting intervention effects in settings of localized cardiovascular disease and critical care [13,14]. In this work, we investigated the application of such models as a tool for monitoring of the left ventricle and systemic circulation in apparently healthy adults at risk of developing cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown promising results for personalizing cardiovascular models [5][6][7][8][9][10][11][12] or predicting intervention effects in settings of localized cardiovascular disease and critical care [13,14]. In this work, we investigated the application of such models as a tool for monitoring of the left ventricle and systemic circulation in apparently healthy adults at risk of developing cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian calibration was considered in Reference 13 to infer boundary conditions and the associated uncertainties in a virtual surgery prediction model and in Reference 14 for lumped parameter models of cardiovascular physiology. In Reference 15, calibration and propagation of uncertainties, where the latter was based on PC expansions, was discussed in a transaortic valve implantation context. In Reference 16, the authors carried out a sensitivity analysis in a preparation step to restrict the calibration procedure to the identifiable parameters of a model for the main pulmonary artery.…”
Section: Introductionmentioning
confidence: 99%